Urethral plate transection for chordee release in severe proximal hypospadias cases - Gokhan Demirtas; Gunay Ekberli; Suleyman Tagcı; Bilge Karabulut; Huseyin Tugrul Tiryaki (Scientific Reports)
Abstract Ventral curvature (VC), and penile straightening is a key step in severe proximal hypospadias surgery. One of the most important variables in selecting the appropriate technique for primary severe hypospadias repair seems to be the urethral plate transection to achieve penile straightening. In some cases, cutting the urethral plate is not sufficient and VC is corrected with ventral corporotomies. In the presented study, it was aimed to evaluate the early results of patients who underwent urethral plate transsection (UPT). Thirty-two cases with severe proximal hypospadias who underwent chordee correction by transsection of the urethral plate between 2019 and 2022 years were evaluated retrospectively. The patients’ ages varied between 8 months and 16 years, with a mean age of 4.61 ± 4.10 years. Ventral curvature was below 90 degrees in 6 patients and above 90 degrees in 26 patients. Penile curvature was corrected by plate transection in 9 children (28.2%) and plate transection combined with ventral corporotomies in 23 children (71.8%). Bracka operation was performed on 8 cases, Duckett operation on 1 case, STAG operation on 8 cases, and STAC operation on 15 cases. We noted recurrence of curvature in 7 children (Bracka 3, STAG 2, STAC 2) which required dorsal plication during the urethroplasty. Second/third stage was completed in all children. Success, hematoma, fistula, meatal stricture, glanuler dehisence, graft stricture rates determined to be 53.2%, 6.25%, 12.5%, 12.5%, 6.25% and 9.37% respectively. Staged procedures give the oppurtunity to correct the residuel or recurrence curvature before urethroplasty. Follow up is important to address long term functional results of ventral corporotomies.